MIKROPROPAGASI UBI JALAR UNGU (Ipomoea blackie) DENGAN MENGGUNAKAN BENZYL AMINO PURIN (BAP) DAN INDOLE 3 BUTYRIC ACID (IBA) SECARA IN VITRO SEBAGAI SUMBER BELAJAR KONSEP BIOTEKNOLOGI BAGI SISWA SMA - Imam Mahadi '; Sri Wulandari '; Berlian Kumala ' (Program Studi Pendidikan Biologi, 2015)
The experiment was conducted at the Laboratory of Biotechnology Faculty of Agriculture, Islamic University of Riau Pekanbaru. In the month of September 2013 - January 2014, with the aim to determine mikropropagasi purple sweet potato (Ipomoea blackie) using BAP and IBA in vitro using Murashige Skoog medium (MS) on the growth of primordial shoots and roots. Parts of the plant which will be used as explants is to take part tuber meristematic tissue concentrations of BAP (0, 1, 1.5, 2, and 3 mg/l) and IBA (0, 0.5, 1, and 2 mg/l). The results showed that there were differences in the growth of explants due to the addition of growth regulators BAP and IBA. Time appears primordial shoots fastest is on treatment (BAP 1.5 + IBA 2 mg/l) with a time of 14 HSK (day after culture) while for the roots of the fastest emerging waktul on treatment (1 BAP + IBA 2 mg/l) with 18 HSK time. BAP and IBA treatment at this concentration has been balanced for growth of purple sweet potato explants. The results of this study will be integrated as a learning resource for high school students of class XII in particular on material in the form of tissue culture techniques Student Task Sheet (LTS).Key Words : Mikropropagasi, Ipomoea blackie, BAP, IBA, sumber belajar